Transcription-repair coupling determines the strandedness of ultraviolet mutagenesis in Escherichia coli. - Oller, A R (1992)
We have analyzed the spectra of UV-induced mutations in the lacI gene of a wild-type and an mfd strain of Escherichia coli. mfd strains have been recently proposed to be deficient in a factor coupling DNA repair and transcription. Analysis of UV-induced mutations occurring at adjacent pyrimidines showed that mutations in the wild-type strain arose largely from the nontranscribed strand but arose predominantly from the transcribed strand in the mfd strain. The overall strand switch was 14-fold. One mutation, G.C-->A.T in the lacI initiation codon, showed a > 300-fold shift. No effect was observed for mutations at non-pyrimidine-pyrimidine sequences. These results provide in vivo evidence for a key role of the mfd gene in controlling the strandedness of mutagenesis and support the proposed role of the mfd gene product in directing DNA excision repair to the transcribed strand of a damaged gene.